High Throughput In–Situ Temperature Sensor Array with High Sensitivity and Excellent Linearity for Wireless Body Temperature Monitoring. Issue 9 (28th June 2022) - Chen, Lei; Yao, Xingye; Liu, Xingchi; Luo, Zewei; Ye, Changqing; Huang, Chengfeng; Wang, Chaolun; Cai, Chunhua; Lyu, Liangjian; Wu, Xing; Bi, Hengchang
Abstract : High sensitivity, excellent linearity, and wireless monitoring are strongly desired for the practical application of flexible temperature sensors in real‐time wearable health care. Especially the multichannel body temperature monitoring system has high requirements on the performance of the sensor because it needs to monitor a large amount of data at the same time. Herein, a flexible temperature sensor based on a porous graphene/polydimethylsiloxane sensing layer is developed. The prepared sensor exhibits high sensitivity of 5.203% °C −1 for temperature sensing between 30 and 70 °C, and excellent linearity (R 2 = 0.996) in the temperature range from 30 to 70 °C. Based on its excellent performance, the proposed high‐performance temperature sensors can be applied in practical applications such as body temperature monitoring and human breath monitoring under different states including slow breath, normal breath, and fast breath. Moreover, a high‐throughput wireless body temperature monitoring system including wireless sensor modules, a cloud server, and a portable electronic device is constructed, which can achieve a remote and multichannel body temperature monitoring efficiently. Abstract : The flexible temperature sensors based on porous graphene/polydimethylsiloxane sensing layer show high sensitivity and excellent linearity. It can be used for respiratory monitoring under different respiratory rates. Moreover, a high‐throughput wireless body temperature monitoring system including wireless sensor modules, a cloud server, and a portable electronic device is constructed, which could achieve a remote and multichannel body temperature monitoring efficiently.